1993
DOI: 10.1159/000187218
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Metabolism in Uremic Rats: A <sup>31</sup>P-Magnetic Resonance Study

Abstract: The effect of uremia on skeletal muscle metabolism of the rat was examined using 31P-magnetic resonance spectroscopy. Three weeks following either a 5/6 nephrectomy or a sham operation, Wistar rats were placed in a 7T magnet, and the sciatic nerve was stimulated for 10 min. Analysis of spectra allowed calculation of intracellular pH and the relative concentrations of phosphocreatine (PCr), inorganic phosphate (Pi) and ATP. [ADP] was calculated from the creatine kinase equilibrium. There was a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“…How ever, it is reduced when measured in the presence of Hepes solution; this has to be intepreted as a consequence of depressed Na+/H + exchanger activity which is more directly demonstrated by a lesser decrease in the patient than in controls of pHj after exposure of lymphocytes to the specific Na+/H + exchanger inhibitor EIPA, and by a lower recovery rate from an induced intracellular acido sis. Normal pHj as indicated by HCO3/CO2 studies is in agreement with 31P-NMR studies in uremic rats [12] and men [9,10] showing that muscle cells maintain pH; within normal ranges despite extracellular metabolic acidosis. Using the same 31P-NMR technique, Monti et al [3] found a lower pHj in uremic HD patients; however, this study was performed in erythrocytes, in which pH; may be less tightly regulated, and more influenced by extracellu lar pH than in other nucleated body cells [25].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…How ever, it is reduced when measured in the presence of Hepes solution; this has to be intepreted as a consequence of depressed Na+/H + exchanger activity which is more directly demonstrated by a lesser decrease in the patient than in controls of pHj after exposure of lymphocytes to the specific Na+/H + exchanger inhibitor EIPA, and by a lower recovery rate from an induced intracellular acido sis. Normal pHj as indicated by HCO3/CO2 studies is in agreement with 31P-NMR studies in uremic rats [12] and men [9,10] showing that muscle cells maintain pH; within normal ranges despite extracellular metabolic acidosis. Using the same 31P-NMR technique, Monti et al [3] found a lower pHj in uremic HD patients; however, this study was performed in erythrocytes, in which pH; may be less tightly regulated, and more influenced by extracellu lar pH than in other nucleated body cells [25].…”
Section: Discussionsupporting
confidence: 85%
“…However, other investigations in man [6][7][8][9][10] and in animals [1 1 , 1 2 ] have found normal pH; in uremia.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the end-of-exercise PCr consumption, when scaled to the total work output, was significantly higher in patients. Similarly to data previously reported in both humans and rats, the rates of both PCr degradation and glycogenolysis declined with time throughout exercise whereas oxidative contribution to ATP production increased so that ATP turnover became virtually all oxidative by five minutes of exercise (13,27).…”
Section: Discussionsupporting
confidence: 81%
“…Acute and chronic anemia are associated with increased arterial lactate concentrations for a given metabolic rate (18);and more specifically, graded reduction in [Hb] is associated with increased skeletal muscle lactate output during exercise (17). However, there are no differences in resting or exercise skeletal muscle pl-l, as a function of anemia in rat (19) or human (20). Finally, no relationship was found between [Hb] and either resting pl-l, or its threshold in the current study.…”
Section: Discussionmentioning
confidence: 99%